The Influence of Employee Performance on Public Satisfaction at the Dawarblandong Sub-District Office, Mojokerto Regency - Naimahtus, Dina Naimahtus; Ningtyas, Veronica Aditya Rahayu Ningtyas; Nahdiah, Emil Nahdiah; Styawan, Trio Adi Styawan (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This study aims to analyze the influence of employee performance on public satisfaction at the Dawarblandong District Office, Mojokerto Regency. Employee performance is measured based on the AMO (Ability, Motivation, Opportunity) theory which assesses ability, motivation, and job opportunities as the main factors influencing individual performance in an organization. The method used is quantitative with a survey approach through the distribution of questionnaires to 83 respondents who are recipients of public services at the district office. The results of the analysis using the Partial Least Squares (PLS) model show that employee performance has a significant and positive effect on public satisfaction with a path coefficient of 0.626 and a p-value <0.05. This indicates that improving the quality of employee performance, both in terms of professionalism, service attitude, and work efficiency, contributes directly to the level of public satisfaction. This study provides theoretical implications for the development of public administration science as well as practical recommendations for improving service quality at the local government level. Keywords: Employee Performance, Public Satisfaction, Public Service